Form Specific : ArtEast Exhibition. - Badovinac, Zdenka (Ljubljana : Moderna Galerija Ljubljana - Museum of Modern Art, 2003)
Avvakumov, Yuri ; Bulloch, Angela ; Buren, Daniel ; EXAT 51 ; Gillick, Liam ; Krasinski, Edward ; Lambri, Luisa ; Lulic, Marko ; Mercier, Mathieu ; Morris, Sarah ; Nicolai, Olaf ; Oiticica, Hélio ; Peljhan, Marko ; Pogacar, Tadej ; Potrc, Marjetica ; Pumhösl, Florian ; Rehberger, Tobias ; Sustersic, Apolonija ; Tati, Jacques ; Vidokle, Anton ; Vukotic, Dusan
biog., ind. tent., gr. tent. p. 194-203, Tekst per kunstenaar/ verschillende auteurs
Sloveens
Engels
Exhibition. Form Specific ArtEast Exhibition. Ljubljana. Moderna Galerija Ljubljana - Museum of Modern Art. 31.05.2003 - 31.07.2003
boek